2016
DOI: 10.2807/1560-7917.es.2016.21.12.30176
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of invasive meningococcal disease of serogroup C / clonal complex 11, Tuscany, Italy, 2015 to 2016

Abstract: We report an increase of serogroup C Neisseria meningitidis invasive meningococcal disease in Tuscany. From January 2015 to end February 2016, 43 cases were reported, among which 10 were fatal, compared to two cases caused by serogroup C recorded in 2014 and three in 2013. No secondary cases occurred. Thirty–five strains belonged to C:P1.5–1,10–8:F3–6:ST-11(cc11). Control measures have been adopted and immunisation campaigns implemented. Studies on risk factors and carriage are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 7 publications
3
43
0
2
Order By: Relevance
“…Immunisation campaigns have been implemented as a result, continuously adapting them to the evolution of the epidemiological situation, and IMD surveillance activities have been enhanced. 7 MenC is the second most common serogroup in Italy (accounting for 31% of the 115 cases with a known serogroup in 2014) after MenB (with 48% of the 115 cases in 2014), while MenY is the third cause of meningococcal infection (13% of the serogroups typed in 2014). 8 Based on 2014 data, in Veneto (northeast Italy) the incidence of IMD is 0.35/100 000 population.…”
Section: Introductionmentioning
confidence: 99%
“…Immunisation campaigns have been implemented as a result, continuously adapting them to the evolution of the epidemiological situation, and IMD surveillance activities have been enhanced. 7 MenC is the second most common serogroup in Italy (accounting for 31% of the 115 cases with a known serogroup in 2014) after MenB (with 48% of the 115 cases in 2014), while MenY is the third cause of meningococcal infection (13% of the serogroups typed in 2014). 8 Based on 2014 data, in Veneto (northeast Italy) the incidence of IMD is 0.35/100 000 population.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of infant rats with the wild-type strain caused severe bacteremia, while an isogenic mutant strain defective in capsule synthesis (but expressing a sialylated LOS) caused bacteremia only when a 10 6 -CFU-higher bacterial dose was used. In addition, when infant rats were infected with encapsulated meningococci that were unable to sialylate the LOS, bacteremia could never be induced, even with an infective dose as high as 10 8 CFU, suggesting that both forms of sialic acid on the bacterial cell surface are indispensable for systemic meningococcal survival in the infant rat model (7). Our study further expands these data to CNS infection dynamics, having in mind, however, all the limitations of an i.c.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, since January 2015, in Tuscany, Italy, there has been an unexpected increase in cases of invasive meningococcal disease (a total of 43 cases, of which 10 were fatal) due to infection with serogroup C N. meningitidis. Thirty-five out of the samples analyzed in this study were confirmed as C:P1.5-1,10-8:F3-6:ST-11 (clonal complex [CC] 11) (8).…”
mentioning
confidence: 82%
“…The lack of statistical significance associated with the perception of dangerousness of meningitis between the two groups, could be attributed on one hand, to the media's echo that it has had in recent years. In fact, as happens during epidemic events, even during the recent meningitis emergency in Tuscany [25,26], it led health authorities to use also the mass media as institutional channels (which in our study were classified as "not institutional") for their rapidity and capillarity to reach the population. On the other, it could be attributed to the intrinsic high outrage level of meningococcal diseases, as recently evidenced [27].…”
Section: Discussionmentioning
confidence: 92%